Pengaruh Return on Asset, Current Ratio, Debt to Equity Ratio dan Arus Kas Operasi Terhadap Dividen Payout Ratio (studi empiris pada perusahaan sub sektor perdagangan eceran yang terdaftar di Bursa Efek Indonesia) : Pengaruh Return on Asset, Current Ratio, Debt to Equity Ratio dan Arus Kas Operasi Terhadap Dividen Payout Ratio (studi empiris pada perusahaan sub sektor perdagangan eceran yang terdaftar di Bursa Efek Indonesia) - Nabilla Egridtya Firnanda Egrid; Slamet Mudjijah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study aims to examine the effect of Return on Asset, Current Ratio, Debt to Equity Ratio and Operating Cash Flow to Dividend Payout Ratio. The population in this study are companies sub-sector retail listed on the Indonesia Stock Exchange for the 2016-2020 period. The analytical technique used is the classical assumption test and multiple linear regression with the help of the SPSS 26 application. The results of the study show that Return on Asset, Current Ratio, and Operating Cash Flow have an effect on the Dividend Payout Ratio. Meanwhile, the Debt to Equity Ratio has no effect on the Dividend Payout Ratio.